Кислотно-основное взаимодействие в сиситеме MgF₂-AlF₃-NaF и его влияние на свойства тонкопленочных покрытий - Зинченко, В.Ф.; Кочерба, Г.И.; Соболь, В.П.; Мозговая, О.В. (Вісник Українського матеріалознавчого товариства, 2017)
Character of phase equilibria in systems MgF₂ – AlF₃ and MgF₂ – Na₃AlF₆ is investigated and their substantiation from positions of the concept of acidity – alkalinity is carried out. It is established that additives of volatile aluminium fluorides (AlF₃, Na₃AlF₆) promote reception of X-ray amorphous coatings with smaller, than at initial MgF₂, mechanical strength.